Genetic alterations in peritoneal metastatic tumors predicted the outcomes for hyperthermic intraperitoneal chemotherapy - Nguyen, Quynh-Anh; Chou, Wan-Hsuan; Hsieh, Mao-Chih; Chang, Che-Mai; Luo, Wei-Tzu; Tai, Yu-Ting; Chang, Wei-Chiao (Frontiers in Oncology, 2023)
Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are considered for patients with peritoneal metastasis (PM). However, patient selection that relies on conventional prognostic factors is not yet optimal. In this study, we performed whole exome sequencing (WES) to establish tumor molecular characteristics for patients and we expect to understand prognosis profiles for PM management. In this study, blood and tumor samples were collected from patients with PM before HIPEC. Tumor molecular profiles were determined using WES. The patient cohort was divided into responders and non-responders according to 12-month progression-free survival (PFS). Genomic characteristics between the two cohorts were compared to identify potential targets. In total, 15 patients with PM were enrolled in this study. Patients who relapsed within 12 months following CRS/HIPEC had significantly worse overall survival (OS, p = 0.015). Driver genes and enriched pathways were identified from WES data. Importantly, AGAP5 was found to have mutated in all responders and was significantly associated with better OS (p = 0.00652). In conclusion, we identified prognostic markers that might be useful to facilitate decision-making before CRS/HIPEC.